Comparative role of affective–Cognitive behavior therapy and jacobson's progressive muscular relaxation in managing pain among patients with fibromyalgia - M T Lakshmi Saranya; R Sreehari; C B Mithun; P I Sangeetha (Indian Journal of Rheumatology, 2023)
Background: Fibromyalgia (FM) is a rheumatologic disease that advances with chronic pain and disability and represents one of the most common causes of chronic and diffuse pain in the population. Objective: An observation study was conducted to compare the role of an individually administered form of Affective Cognitive Behavioural Therapy (ACBT) with Jacobson's Progressive Muscular Relaxation (JPMR) in changing the scores of Pain and FM impact among patients with FM. Method: Patients receiving ACBT and JPMR were allocated to two groups by licensed clinical psychologists until each group had a sample of 10 each. Both groups received 6 individual sessions (once in every two weeks). A baseline assessment was done to assess the Pain and FM impact prior to the intervention. Post and follow up assessments were carried one week and one month after the intervention respectively. Post scores of both groups were compared with baseline scores. Results: The current study revealed that ACBT is associated with impressive improvements in Pain reduction and FM Impact among the patients with FM. Conclusion: Considering the effect of ACBT in reducing the Pain and FM Impact scores, ACBT shall be considered as an add-on psychological intervention along with the pharmacological management to yield better outcomes in FM patients. However, more research including randomized control trails are required to confirm its effectiveness.